Sound absorption performance of EFBMF panel for building acoustic material - Samsudin, Emedya Murniwaty (2018)
For decades synthetic materials have been widely used as acoustic absorbers for building. However their adverse effects to humans and the environment have led to the use of natural materials. This research aims to introduce two sources of natural fibers from palm oil residues as an acoustic material. Empty fruit bunches (EFB) and mesocarp fibers (MF) were mixed with commercial wood binder to form panels for acoustic applications. Different forms of fibers and 11 mixes were used ranging from 10 mm to 50 mm thickness. Absorbency of EFBMF was measured following ISO 10534 Part 2, while selected panels were further tested for its practical performance following ISO 354 and classified as a building absorber according to the ISO 11654. Analyses were done to signifies the relationship between thickness, bulk density and apparent porosity of EFBMF panels towards noise reduction coefficient (NRC) values. Empirical study evidenced that as EFBMF samples goes thicker, its density will increased and porosity will decreased, thus resulting in high NRC value. Validation through theoretical study approved that thicker samples owned higher density due to more fiber content and causing the perforation inside the material to reduced and leads to high flow resistivity. This will results in higher sound energy to be converted to heat and resulting in higher absorption. Absorption performance of EFBMF panel achieved 0.58 coefficients with optimum thickness, bulk density and apparent porosity value of 4.5 cm, 0.375 g/cm3 and 65.5 % respectively. Practical performance of EFBMF panel is at 90 % absorbing for 100 MF coir panel, 85 % absorbing for 90:10 coir panel and 80 % absorbing for the other three (3) panels (50:50 coir, 100 EFB dust and 80:20 dust) in the reverberation chamber. In conclusion, EFB and MF wastes are another viable alternative raw fibers that is capable to be use in many application such as for reverberation control, noise control, echo control and as a sound insulation for building.